Prevalence of self-medication and associated factors among female students of health science colleges at Majmaah University: A cross-sectional study - Loni, Shamshad Begum; Eid Alzahrani, Raed; Alzahrani, Mansour; Khan, Mohammad Owais; Khatoon, Rafia; Abdelrahman, Huda Hakim; Abd-Elhaleem, Zeinab A.; Alhaidari, Munira Mohammed (Frontiers in Public Health, 2023)
Introduction Globally, the prevalence of self-medication among young people has increased exponentially. Due to the basic knowledge and easy access to medicines, undergraduate students at health science colleges are likely to self-medicate. This research was undertaken to assess self-medication prevalence and its contributing factors among female undergraduate students in health science colleges at Majmaah University, Saudi Arabia. Materials and methods A descriptive, cross-sectional study involving 214 female students from the Majmaah University in Saudi Arabia's health science colleges—Medical: (82, 38.31%) and Applied Medical Science College (132, 61.68%)—was conducted. A self-administered questionnaire with sociodemographic information, drugs used, and reasons for self-medication was used for the survey. Non-probability sampling techniques were used to recruit participants. Results Of the 214 female participants, 173, 80.84 % (medical: 82, 38.31% and applied medical science: 132, 61.68%) confirmed that they were on self-medication. The majority of participants (42.1%) were between the ages of 20 and 21.5 years (mean ± SD: 20.81 ± 1.4). The main reasons for self-medication were quick relief from the illness (77.5%) followed by saving time (76.3%), minor illnesses (71.1%), self-confidence (56.7%), and laziness (56.7%). The use of leftover drugs at home was common among applied medical science students (39.9%). The main indication for self-medication included menstrual problems (82.7 %), headache (79.8%), fever (72.8%), pain (71.1%), and stress (35.3%). The most common drugs used included antipyretic and analgesics (84.4%), antispasmodics (78.9%), antibiotics (76.9%), antacids (68.2%), multivitamins, and dietary supplements (66.5%). On the contrary, the least used drugs were antidepressants, anxiolytics, and sedatives (3.5, 5.8, and 7.5 %, respectively). Family members were the main source of information for self-medication (67.1%), followed by self-acquired knowledge (64.7%), social media (55.5%), and least were friends (31.2%). For adverse effects of the medication, the majority of them consulted the physician (85%) followed by consulting the pharmacist (56.7%) and switched to other drugs or decreased drug dosage. Quick relief, saving time, and minor illness were the main reasons for self-medication among health science college students. It is recommended to conduct awareness programs, workshops, and seminars to educate on the benefits and adverse effects of self-medication.